РАҚАМЛИ ДАВЛАТ СТРАТЕГИЯСИНИ ШАКЛЛАНТИРИШДА МИЛЛИЙ ХАВФСИЗЛИКНИ ТАЪМИНЛАШ - Сатторов, Н.О. (SCIENCE and SOCIETY, 2024)
The article discusses the new format of close cooperation between society and diplomatic agencies. The author gives a brief history of digital diplomacy and shows its mechanism of influence on foreign audiences. The ongoing information technology and content revolution in the media at a time when the influence of Inernet, manipulation of public opinion and the possibility of managing large groups of people, including for political purposes, has increased significantly, under a number of key indicators, complicates the interaction of participants in international relations and opens up new opportunities for the policy of "soft power"